2000
DOI: 10.1127/0935-1221/2000/0012-0955
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and compressibilities of synthetic 2M1 and 3T phengite micas

Abstract: Abstract:The crystal structures of co-existing monoclinic 2M 1 and trigonal 3T polytypes of phengitic micas synthesized at 11 GPa and 900 ºC have been refined at ambient conditions. The compositions of both . The molar volumes of the two polytypes are identical within error (approximately one part in 4000). The structures show closely similar distortions consistent with the nearly pure silicate tetrahedral layer. The tetrahedral rotation angles, α, are both about 2.4º and thus the smallest yet reported for dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 20 publications
2
47
0
Order By: Relevance
“…Previous experiments were confined to the investigation of the unitcell parameters with P, and were aimed to describe the isothermal EoS and the phase-stability of 2M 1 -and 3T-phengites (Pavese et al, 1999;Smyth et al, 2000, Curetti et al, 2006.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous experiments were confined to the investigation of the unitcell parameters with P, and were aimed to describe the isothermal EoS and the phase-stability of 2M 1 -and 3T-phengites (Pavese et al, 1999;Smyth et al, 2000, Curetti et al, 2006.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…To date, only a few studies have been devoted to the high-pressure (HP) behaviour of dioctahedral micas (Vaughan and Guggenheim, 1986;Sekine, Rubin, Ahrens, 1991;Faust and Knittle, 1994;Catti, Ferraris, Hull, Pavese, 1994;Comodi and Zanazzi, 1995;1997) and in particular of phengites (Pavese, Ferraris, Pischedda, Mezouar, 1999;Smyth, Jacobsen, Swope, Angel, Arlt, Domanik, Holloway, 2000;Curetti, Levy, Pavese, Ivaldi, 2006). Pavese et al (1999) described the thermo-elastic behaviour of a natural 3T-phengite by in-situ synchrotron X-ray powder diffraction with a Paris-Edinburgh cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analytical absorption correction was applied using the indexed shape and measured dimensions of the crystal (Sheldrick, 1997). The structure was refined in space group C2/c using neutral-atom scattering factors from the International X-ray Crystallographic Tables (1973), and initial atom positions of Smyth et al (2000).…”
Section: Muscovite Origin and Bulk Structure Refinementmentioning
confidence: 99%
“…The cubic unit cell parameter of ringwoodite was refined using the Rietveld program GSAS (Larson and von Dreele, 2000) and reported in Table 1 . In a single-crystal compression study Smyth et al (2000) observed a K´ value of 9 for two polytypes of phengite mica. We have also obtained a bulk modulus of 146 GPa with K' of 6.1 in a singlecrystal compression study of hydrous wadsleyite II (Smyth et al 2005).…”
Section: Experimental Methodsmentioning
confidence: 99%